Β-glucan extracted from eukaryotic single-celled microorganism Saccharomyces cerevisiae: Dietary supplementation and enhanced ammonia stress tolerance on Oreochromis mossambicus. (February 2020) - Divya, Mani; Gopi, Narayanan; Iswarya, Arokiadhas; Govindarajan, Marimuthu; Alharbi, Naiyf S.; Kadaikunnan, Shine; Khaled, Jamal M.; Almanaa, Taghreed N.; Vaseeharan, Baskaralingam
Abstract: Ammonia is a widespread pollutant that is toxic to living organisms in aquaculture. This study aimed to evaluate the effects of a diet supplemented with beta-glucan from yeast, Saccharomyces cerevisiae ( Sc-βG ), on the stress response of Oreochromis mossambicus (Tilapia) to ammonia. Fish were divided into four groups, including a control fed a basal diet and three experimental groups fed diets supplemented with Sc-βG at 2, 5 and 10 mg/g respectively. After 8 weeks, experimental groups were exposed to ammonia at 100 mg L −1 for 1 week. Growth was measured after the 8-week feeding trial and serum, mucus, and liver tissue were sampled before and after the ammonia challenge. Compared with the control diet, feed supplemented with Sc-βG at 10 mg/g significantly (p < 0.05) improved growth performance (7.8–9.9 g increase in weight). The cellular immune responses (myeloperoxidase, reactive oxygen species, and reactive nitrogen species), humoral immune responses (alkaline phosphatase, lysozyme, and peroxidase inhibition), and antioxidant response (catalase, superoxide dismutase, and glutathione) were tested in serum, mucus and liver tissue. Compared with the control, these responses were significantly (p < 0.05) enhanced at 10 mg/g supplementation with Sc-βG. This study demonstrates that Sc-βG may be applied to induce stress tolerance and improve growth performance in aquaculture. Graphical abstract: Image 1 Highlights: Β- glucan was extracted from S. cerevisiae ( Sc-βG ) by the alkaline extraction method. It was primarily characterized by XRD to confirm the presence of glucan molecules. Ammonia stress tolerance was enhanced under a β-glucan supplemented diet.